Synergistic effect of PtSe2 and graphene sheets supported by TiO2 as cocatalysts synthesized via microwave techniques for improved photocatalytic activity. Issue 1 (24th September 2014) - Ullah, Kefayat; Ye, Shu; Lei, Zhu; Cho, Kwang-Yeon; Oh, Won-Chun
Abstract : Here we report a new composite material consisting of TiO2 nanoparticles grown in the presence of a layered PtSe2 /graphene hybrid as a high-performance photocatalytic material. Abstract : Here we report a new composite material consisting of TiO2 nanoparticles grown in the presence of a layered PtSe2 /graphene hybrid as a high-performance photocatalytic material. The heterogeneous PtSe2 –graphene/TiO2 nanocomposites were successfully synthesized through a facile and fast microwave-assisted method. The prepared composites were characterized through X-ray diffraction (XRD), scanning electron microscopy (SEM) with energy dispersive X-ray (EDX) spectroscopy, transmission electron microscopy (TEM), Raman spectroscopic analysis, X-ray photoelectron spectroscopy (XPS), and UV-vis absorbance spectra and UV-vis diffuse reflectance spectra (DRS) analyses were obtained. The catalytic behavior was investigated through the decomposition of rhodamine B (Rh. B) as a standard dye and Texbrite MST-L as an industrial dye. This extraordinary photocatalytic activity arises from the positive synergetic effect between the PtSe2 and graphene components in this heterogeneous photocatalyst. In this study the graphene behaves as an electron transfer agent, collector, contributor and a source of active adsorption sites. The optical properties were also observed to be affected by the different weight% of graphene in the composites by observing their respective band gaps from DRS spectra.